Mung Bean and Soy Snack Bars as an Alternative Snack for Athletes - Gerarda Lisa Yuwanti; Veni Indrawati; Choirul Anna Nur Afifah; Lini Anisfatus Sholihah (Universitas Negeri Semarang, 2024)
Snack bars are snacks that are suitable to be consumed after exercise. This research aims to determine the effect of substitution of mung bean flour and addition of soybean flour on the acceptability of a snack bar, as well as the nutritional content of carbohydrates, proteins, and BCAA of the best formula. This research is a pure experiment, with 3x2 factorial research design. The panelists consist of 35 untrained panelists, namely 35 inkai karate athletes at ADLI KBD. The research data were obtained by filling out organoleptic acceptability test questionnaires, then analyzed with Friedman and Wilcoxon test. While the nutritional content is obtained through laboratory tests. The substitution of mung bean flour and the addition of soybean flour significantly affect the aroma (p=0.02), texture (p=0.00), and taste (p=0.00); But it does not significantly affect the color (p=0.40). The best formula were the substitution of 10% mung bean flour and the addition of 5% soybean flour. A piece of snack bar (50g) contains 28.05g carbohydrates; 7.03g protein; and 28.47mg BCAA (10.52mg leucine; 12.05mg isoleucine; 5.9mg valine). One snack bar can fulfill 77,2% of carbohydrates and 72,8% protein needs. Athletes need to consume two pcs after exercise to reach 10% of their daily nutrition needs.